The Effect of Planned Behaviour Theory on Agropreneurship Intention: The Moderating Role of Gender / Mohd Nur Fikri Waktu Saptu, Sylvia Nabila Azwa Ambad and Viduriati Sumin - Waktu Saptu, Mohd Nur Fikri; Ambad, Sylvia Nabila Azwa; Sumin, Viduriati (Research Management Centre (RMC), 2020)
Agriculture is the second largest contributor to Sabah's Gross Domestic Product (GDP), with an average contribution of 24% annually. It is also proven in many third world countries that investment in agriculture plays a crucial role in poverty reduction, providing more job opportunities, and ensuring food security. Sabah recorded the highest rate of unemployed youth in 2018 and remained as the state with the highest score of hardcore poor people in Malaysia; thus, Sabah will be economically benefited from agricultural growth. However, the number of youth participation in the agriculture sector is still low at a rate of approximately 15%. Agricultural entrepreneurship or also known as agropreneurship among youth, needs to be broadened to promote greater opportunities in the agriculture sector. Therefore, using the Theory of Planned Behaviour (TPB), this research examines agropreneurship intention and the moderating effect of gender among youth in Sabah, Malaysia. A total of 382 youth participated in the survey. Partial Least Squares-Structural Equation Modeling 3.0 was used to analyse the collection of data. The results found that attitude of the youths towards agropreneurship and perceived behavioural control have a positive effect on agropreneurship intention. Meanwhile, subjective norms did not have a significant effect on agropreneurship intention, and gender has no moderating effect. In line with the first Sabah Agriculture Blueprint 2021-2030, this study intends to contribute to the formulating of policies and relevant programmes, especially in accelerating agropreneurship participation. It also contributes to Sabah's aspiration of becoming a hub for the agriculture sector in this region